2008
DOI: 10.2190/de.38.3.g
|View full text |Cite
|
Sign up to set email alerts
|

Salvia DivinorumUse among a College Student Sample

Abstract: The recreational use of Salvia divinorum has received increased attention by media outlets and policy-makers in recent years. The vast absence of research to guide the dissemination of information has prompted this research note describing the use of this substance in a large public institution of higher education. The prevalence of Salvia divinorum is described in this context and a description of patterns of use, methods of acquisition, and a subjective estimation of continuance are proffered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 10 publications
2
31
2
Order By: Relevance
“…Use of bath salts was found to be more common among Hispanics and Native Americans as compared to Whites and Blacks. This is in contrast to other studies that have indicated novel drug use is more common among Whites (Lange et al 2008;Khey et al 2008). Those studies, however, focused on non-stimulant drugs.…”
Section: Discussioncontrasting
confidence: 72%
“…Use of bath salts was found to be more common among Hispanics and Native Americans as compared to Whites and Blacks. This is in contrast to other studies that have indicated novel drug use is more common among Whites (Lange et al 2008;Khey et al 2008). Those studies, however, focused on non-stimulant drugs.…”
Section: Discussioncontrasting
confidence: 72%
“…Respondents’ age, sex, race/ethnicity (non-Hispanic white, non-Hispanic black, Native American [American Indian/Alaska Native], Asian/Pacific Islander/Native Hawaiian, multiple-race, Hispanic), total family income, and population density of residence were examined as potential correlates for S. divinorum use 17,21,22,3133. For adolescents who were unable to respond to the income questions, proxy responses were accepted from a household member.…”
Section: Methodsmentioning
confidence: 99%
“…To date, there are only a few studies of prevalence and correlates of S. divinorum use, and they have focused primarily on college students 17,21,22. In a convenience sample of undergraduate students at a large public university in the southeastern United States (N = 825), 10.9% of men and 3.8% of women reported lifetime use of any S. divinorum; S. divinorum use was associated with male sex, white race, a high level of family income, marijuana use, and a low level of self-control 17,21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SD is controlled in 20 US states (Drug Enforcement Administration, 2012) and is listed as a "drug of concern" by the US Drug Enforcement Administration (DEA) (Perron et al, 2012). SD is legally and commercially available in many states and countries, which likely contributes to its popularity (Khey et al, 2008). In 2012, 5.2 million individuals in the US (2% of the population) were estimated to have used SD in their lifetime, with highest use rate among young males (SAMHSA, 2012).…”
Section: Introductionmentioning
confidence: 99%